Efektifitas Massage Deep Friction dan Latihan Stabilisasi Trunk Pada Cerebral Palsy - Suharto; Suriani (Yayasan Literasi Sains Indonesia, 2022)
Cerebal Palsy is a permanent disorder in the development of movement and non-progressive body posture in the form of muscle tone abnormalities that cause postural tone disorders in the form of spasticity, especially in the legs, sitting balance so that the patient's daily functional activities are disrupted. This study aims to determine the effect of deep friction massage and trunk stabilization exercises on sitting balance and spasticity in cerebral palsy patients. This type of research is a pre-experiment with a one-group pre-test-post-test design. It was held at the Makassar special school from August to October 2018, with a research sample of 17 cerebral palsy patients. Sitting balance data was obtained using a pediatric balance scale and leg spasticity data was obtained using the Asworth scale. The results of the Paired sample T Test obtained p = 0.000 for spasticity and sitting balance with p = 0.000 after being given deep friction massage and trunk stabilization exercises. Thus deep friction massage and trunk stabilization exercises are effective in improving sitting balance and spasticity in cerebral palsy patients.